This is how a third world war can be avoided - Henry Kissinger (The college of law and political science journal, 2025)
In a warning issued by the former US Secretary of State and well-known strategic expert (HENRY KISSINGER) in an interview conducted with him by the British magazine (THE ECONOMIST) on May 17, 2023, in which he presented ideas for what he called “avoiding the outbreak of a third world war” and expectations about the outbreak of a third world war, where he touched on the dangers of not taking bold and clear steps to prevent all of this from happening.